Employee Performance in the Digital Banking Era: The Mediating Role of Engagement in Linking Competence, Culture, and Work Stress - Noviardi Ferzi; Albetris Albetris; Muhammad Akbar (Global Research and Collaboration, 2026)
This study examines the mechanisms through which human resource competence, organizational culture, and work stress influence employee performance, with employee engagement acting as a mediating variable. Drawing upon Human Capital Theory, Job Demands–Resources (JD-R) Theory, and Social Exchange Theory, this research proposes an integrated framework to explain employee performance within the context of digital transformation in the banking sector. A quantitative explanatory design was employed, with data collected from 250 employees of a regional development bank using proportionate stratified random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that human resource competence and organizational culture have positive and significant effects on both employee engagement and employee performance. In contrast, work stress negatively affects employee engagement but does not have a significant direct effect on employee performance. Furthermore, employee engagement emerges as the strongest predictor of performance and functions as a full mediator in the relationship between work stress and employee performance, while serving as a partial mediator in the relationships involving human resource competence and organizational culture. This study contributes to the literature by integrating structural and psychological perspectives into a unified framework and by providing empirical evidence from a relatively underexplored context. The findings offer important strategic implications for organizations seeking to enhance employee performance through engagement-driven human resource management practices.